2019
DOI: 10.1108/ecam-12-2018-0535
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the use of integrated project delivery (IPD): a quantified model for Malaysia

Abstract: Purpose The purpose of this paper is to quantify the barriers to the use of integrated project delivery (IPD), as assessed by 115 construction professionals in Malaysia. Design/methodology/approach Barriers recording highest citation amongst researchers worldwide were collated in the form of a conceptual model. This model was validated via a partial least squares structural equation modelling technique. Findings Findings advance the body of knowledge on IPD by providing original insights into the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 67 publications
0
54
0
2
Order By: Relevance
“…A similar study by Bryde, Broquetas [33] found that the use of BIM helped to shorten project timescale and was an influential driver for its adoption, particularly due to its ability to conduct early clash detection, resulting in minimization of associated delays and risks during on-site project implementations. Furthermore, BIM could prevent schedule delays, which enhances early completion and returns on investment [6,57].…”
Section: Key Drivers For Bim Implementationmentioning
confidence: 99%
“…A similar study by Bryde, Broquetas [33] found that the use of BIM helped to shorten project timescale and was an influential driver for its adoption, particularly due to its ability to conduct early clash detection, resulting in minimization of associated delays and risks during on-site project implementations. Furthermore, BIM could prevent schedule delays, which enhances early completion and returns on investment [6,57].…”
Section: Key Drivers For Bim Implementationmentioning
confidence: 99%
“…Effective BIM education within HEIs requires cultural change and industry-oriented curricula (Best and Langston 2005) such has yet to be realised (Baradi et al 2018;Jin et al 2019;Mills et al 2013;Puolitaival and Forsythe 2016). Whilst academia may criticise AECO industry practitioners for operating in a traditional manner (Durdyev et al 2019), the irony is that many Australian universities mirror the same ineffective practices. This could be because academics either have minimal industrial experience or that experience is outdated.…”
Section: Previous Researchmentioning
confidence: 99%
“…Além disso, os reais benefícios do IPD em prática ainda são pouco compreendidos na indústria da construção civil (DE MARCO;KARZOUNA, 2018;WHANG;KIM, 2019;TENG et al, 2019). Os limites de conhecimento e aplicabilidade do IPD têm dissuadido a adoção dos seus elementos em ambientes de produção de empreendimentos com pouca experiência com esta prática (LAURENT; LEICHT, 2019;ABDIRAD;DOSSICK, 2019;DURDYEV et al, 2019).…”
Section: Gestão and Tecnologia De Projetosunclassified